Climate Change Migration and the Economic Rebirth of Central Appalachia - Elizabeth C. Hirschman (Social Sciences, 2022)
This research examines the potential economic rebirth of the Central Appalachian Region as persons from the southwestern and southeastern parts of the United States seek a safe and livable environment for their families and businesses. Central Appalachia is projected to be the largest habitable area in the continental United States by the year 2050. However, mined land remediation, water control efforts, and hydro-electric energy generation units will be required to support the incoming population.